2014
DOI: 10.1177/0021998314535456
|View full text |Cite
|
Sign up to set email alerts
|

Self-piercing riveting of aluminum alloy and thermoplastic composites

Abstract: In the present study, the feasibility of joining PA6-matrix thermoplastic composite panel and aluminum alloy is considered. Self-piercing riveting processes of PA6 panels, PA6 composite panels with reinforcing fibers (glass fiber and carbon fiber), and 5754 aluminum alloy sheets are systematically investigated. Macro characterizations of the appearance and transverse sections of the self-piercing riveting joints were conducted to provide more comprehensive understanding of the composite deformation during rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 18 publications
1
19
0
1
Order By: Relevance
“…Their results demonstrated that SPR appeared competitive for metal/polymer joining as to joint strength and cost. Research was also carried out by Zhang and Yang [83] to study the joinability of various thermal plastic polymer PA6-based materials and AA5754. Their results showed that when PA6 and its glass fibre or carbon fibre reinforced composite were used as the bottom material, severe cracking or bottom sheet penetration would happen and the carbon fibre reinforced thermal plastic could not be used as the top sheet due to fracture during the SPR rivet inserting process.…”
Section: Suitable Materials For Spr Joiningmentioning
confidence: 99%
“…Their results demonstrated that SPR appeared competitive for metal/polymer joining as to joint strength and cost. Research was also carried out by Zhang and Yang [83] to study the joinability of various thermal plastic polymer PA6-based materials and AA5754. Their results showed that when PA6 and its glass fibre or carbon fibre reinforced composite were used as the bottom material, severe cracking or bottom sheet penetration would happen and the carbon fibre reinforced thermal plastic could not be used as the top sheet due to fracture during the SPR rivet inserting process.…”
Section: Suitable Materials For Spr Joiningmentioning
confidence: 99%
“…However, because of the physical and chemical dissimilarities of individual materials, the development of suitable joining technologies is essential for enabling multi-material auto bodies. Recently, extensive research has been conducted for joining carbon fiber composites to various metals (e.g., aluminum or magnesium alloys), using laser welding [7,8], friction stir blind riveting [9], friction spot joining [10][11][12], ultrasonic welding [13], adhesive bonding [14], friction lap welding [15,16], friction-based injection clinching joining [17], self-piercing riveting [18,19], and hybrid bonding (adhesive + mechanical fastening) [20][21][22]. In addition, very limited work has been focused on joining carbon fiber composites to steel [8,14,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain optimal connection parameters, they used the FE code DEFORM to simulate the process of SPR, and the deformation mechanism of the joint was predicted by compar-ative analysis of the test results. Zhang and Yang 11) investigated the feasibility of joining the PA6-matrix thermoplastic composite sheet and aluminium alloy sheet. The ef ciency of SPR in joining the Al alloy and GFRP/CFRP composites was examined.…”
Section: Introductionmentioning
confidence: 99%